The influence of geometric nonconformance of the SB4 tension clamps on their strength and elasticity characteristics - Pieniak, Daniel; Guzik, Miroslaw; Lonkwic, Pawel; Lesiak, Piotr; Selech, Jaroslaw; Krzysiak, Zbigniew; Matijosius, Jonas; Sejkorová, Marie; Kilikevicius, Arturas (Nature Publishing Group, 2024)
The paper presents comparative laboratory investigations of tension fastener models that attach rails to concrete sleepers. The aim of the paper was to assess the influence of geometric nonconformity of the actual industrial product that meets the PKP Polskie Linie Kolejowe S.A. requirements on the operation of a tension-fastening clamp under stress. Due to the cost and limited possibility of research of the actual industrial product, an additional objective of the research was to validate the usefulness of it in the comparative assessment of the models. In the research, the authors used models of tension fastening clamps manufactured in incremental engineering technology (3D print) on scale 1:2. The properties of the fastening clamps (in their nominal shape) were compared (described in the PKP Polskie Linie Kolejowe S.A. documentation) with the fastening clamps of the actual shape. In the investigation, the authors have confirmed the negative influence of the non-conformance of the shape of the actual fastening clamps with the nominal ones.
Vliv geometrické neshody tahových svorek SB4 na jejich pevnostní a elastické charakteristiky
Keywords: fatigue performance; rail; speed; optimization; reliability; behavior; system; track; únavový výkon; železniční; rychlost; optimalizace; spolehlivost; chování; systém; dráha